2002
DOI: 10.1002/jgt.10022
|View full text |Cite
|
Sign up to set email alerts
|

Path factors in cubic graphs

Abstract: Let p be a set of connected graphs. An p -factor of a graph is its spanning subgraph such that each component is isomorphic to one of the members in p . Let P k denote the path of order k. Akiyama and Kano have conjectured that every 3-connected cubic graph of order divisible by 3 has a fP 3 g-factor. Recently, Kaneko gave a necessary and suf®cient condition for a graph to have a fP 3 , P 4 , P 5 g-factor. As a corollary, he proved that every cubic graph has a fP 3 , P 4 , P 5 g-factor. In this paper, we prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 3 publications
(2 reference statements)
0
29
0
Order By: Relevance
“…Kawarabayashi et al [11] proved that every 2-connected cubic graph G has a 2-factor in which each component is a cycle of length at least four. Theorem 2.5 (Kawarabayashi et al [11]).…”
Section: Theorem 23 (O and Westmentioning
confidence: 99%
See 1 more Smart Citation
“…Kawarabayashi et al [11] proved that every 2-connected cubic graph G has a 2-factor in which each component is a cycle of length at least four. Theorem 2.5 (Kawarabayashi et al [11]).…”
Section: Theorem 23 (O and Westmentioning
confidence: 99%
“…Theorem 2.5 (Kawarabayashi et al [11]). Every 2-connected cubic graph G has a 2-factor in which each component is a cycle of length at least four.…”
Section: Theorem 23 (O and Westmentioning
confidence: 99%
“…A partial (positive) answer to this was obtained by Kaneko et al [6] who established that every connected n-vertex claw-free graph having at most two end-blocks (in particular, a 2-connected claw-free graph) has a maximum P 3 -matching of cardinality n/3 . Another result concerning Akiyama and Kano's conjecture was obtained by Kawarabayashi et al [7] who showed that any 2-connected cubic graph of at least 6 vertices has a {P n 6 }-factor, and hence a {P 3 , P 4 }-factor. Clearly, this implies the existence of a P 3 -matching of cardinality at least n/4 in this class of graphs.…”
Section: Introductionmentioning
confidence: 95%
“…It follows immediately from Theorem 4 that every connected cubic bipartite graph G of order at most 16 has a Hamiltonian path since G has a {C n |n ≥ 6}-factor, which consists of at most two components, and a graph consisting of two disjoint cycles and one edge joining them has a Hamiltonian path. It is not mentioned in [4] that the conclusion of Theorem 3 is best possible. However, we can easily find 2-connected cubic graphs having no {C n | n ≥ 5}-factors.…”
Section: Theorem 4 (I) Every Connected Cubic Bipartite Graph Has a {Cmentioning
confidence: 99%
“…2 Statement (ii) of Theorem 4 follows immediately from the next Lemma 9 and the statement (i) of Theorem 4. It is shown in [4] that if a 2-connected cubic graph of order at least six has a {C n |n ≥ 4}-factor, then it has a {P n |n ≥ 6}-factor. This statement can be generalized as the following Lemma 9 without changing the proof.…”
Section: Case 1 a Component Of F H Contains The Edge Xymentioning
confidence: 99%